Contemporary approaches to communication skills training: a pre-training investigation - Done, Judith Madeleine (1997)
This study is designed to contribute to the understanding of the theory and practice of communication skills training. The participants are 48 trainee careers advisers following a Postgraduate Diploma in Careers Guidance. The purpose of the research is to investigate the effect of pre-training assessment and feedback on post-training performance. A secondary hypothesis relates to gender differences in communicative competence. The study uses a quasi-experimental, pre- and post-test design in which the independent variables are feedback and training. Dependent variables, applied at Time 1 and Time 2, include four self-report measures (Rotter I-E Scale, Social Situations Questionnaire, PONS Test and a repertory test) and behavioural ratings applied to videotaped interviews by two independent, trained raters. The findings suggest that while neither pre-treatment feedback alone nor training alone has an effect on performance at Time 2, the combination of feedback plus training produces a significant improvement in performance from Time 1 to Time 2. Significant differences between males and females in certain behavioural rating categories were found at Time 2. The results of this study lead the writer to propose that communication skills training could be enhanced by the inclusion of pre-training assessment and feedback, an inclusion which would result in CST being tailored more specifically to individuals even when the training is administered to groups. A second recommendation based on the findings is that there is scope for further investigation into gender differences in communicative behaviour and their implications for training.